DISKURSUS KORUPTOR DALAM MEDIA MASSA: (Analisis Framing Terhadap Pemberitaan Karakter Koruptor Kader Partai Di Kompas Online ‘kompas.com’) - Ahmad Toni; Rocky Prasetyo Jati (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2013)
This study of the discourse in the news framing perspective character kompas.com corruptparty cadres in the online media in Asia, aims to do construction and mapping of a number ofnews character corrupt major parties. Well, the character of the ruling party cadres thatcurrently, many Democratic party cadres entangled in corruption cases, the pro-governmentparty cadres PKB, PKS and PAN, to party cadres themselves as the party of opposition voicedSBY administration, the PDI-P.